Effects of replica running shoes upon external forces and muscle activity during running - da Silva Azevedo, A. P.; Brandina, K.; Bianco, R.; de Oliveira, V. H.; Roque de Souza, J.; Mezencio, B.; Amadio, A. C.; Cerca, Serrão, J. (Journal of Sports Sciences, 2012)
Twelve participants ran (9 km/h) to test two types of running shoes: replica and original shoes. Ground reaction force, plantar pressure and electromyographic activity were recorded. The shoes were tested randomly and on different days. Comparisons between the two experimental conditions were made by analysis of variance (ANOVA) test (P = 0.05). The time to first peak, loading rate of the first peak and impulse of the first 75 ms of stance were significantly different between the shoes (P = 0.05), revealing an increase of impact forces for the replica shoes. The peak plantar pressure values were significantly higher (P = 0.05) when wearing replica shoes. During running, the contact area was significantly smaller (P = 0.05) for the replica shoe. The electromyographic activity of the analysed muscles did not show changes between the two shoes in running. These findings suggest that the use of replica running shoes can increase the external load applied to the human body, but may not change the muscle activity pattern during locomotion. This new mechanical situation may increase the risk of injuries in these movements.